PENGARUH VARIASI MAIN JET NOZZEL PADA SISTEM KARBURATOR TERHADAP UNJUK KERJA MESIN - Alvinsen Alfonso; Abrar Riza; I Made Kartika (Program Studi Teknik Mesin Universitas Tarumanagara, 2017)
Abstract: This study discusses the effect of variations in the diameter of the main jet nozzles on the performance of the motor fuel. Performance analysis covering torque, power and specific fuel consumption (sfc). With the aim to determine the maximum performance that can be generated on any variation of the diameter of the main jet nozzles. At the time of this experiment performed with the engine 4 stroke Honda GX-160, using hydro tool dynamometer and using premium fuel. The data taken is the engine rotation, the force measured on the dynamometer and the time spent fuels. Tests conducted at the Laboratory of Energy Conversion Mechanical Engineering UNTAR Jakarta. Testing is done by providing the machine with a load variation of rotation remains in order to obtain a force on each spin machine with a main jet nozzle diameter variations. Variations rev the engine starts at the minimum rotation until maksimuml with fixed load, variations in the diameter of the main jet nozzles on testing.